The outcome of the use of custom made antibiotic cemented nail in management of chronic diaphyseal osteomyelitis - Sharma, Sushil; Wahegaonkar, Krishna; Dware, Prakash (Grande Medical Journal, 2024)
BackgroundChronic osteomyelitis of long bone is a difficult condition to treat. Local delivery of antibiotics via custom-made antibiotic cemented nail(ACN) enables delivery of antibiotics at high concentration, which helps in eradication of infection and provides mechanical stability in infected nonunion. The study aims to find out the role of ACN in the control of infection and union of long bones.Method30 patients presenting with the feature of chronic osteomyelitis of long bones & infected non union between 2014 and 2017 at Manipal Teaching Hospital were included. Cases were treated with debridement, sequestrectomy, and the use of ACN. Follow-up of patients was done till control of infection and union. Patients were assessed clinically and on laboratory parameters for control of infection & union.ResultAmong 30 patients, 13 (43%) were infected nonunion, 6 (20%) were of osteomyelitis following open fracture, 5 (17%) were of osteomyelitis following soft tissue procedure and 6 (20%) were of open fracture where ACN was used prophylactically. Infection control was achieved in 28 (93%) cases. The average time of radiological union was 12 months. The average duration of removal of ACN was 7.4 weeks. Complications included the failure of removal of antibiotic cement in one (3%) case & failure of union in one (3%) case.ConclusionACN is an economical method that can be used safely in the management of chronic osteomyelitis of long bones. The technique is simple, cost-effective with excellent results, minimal complications, and can be used in a minimal resources setting.